Equilibrium, kinetics and thermodynamics of biosorption of U(VI) by Jonesia quinghaiensis strain ZFSY-01 isolated from the wastewater of a uranium mine - Gen Xie; Henglei Chen; Peihong Mao; Guangwen Feng (IWA Publishing, 2023)
The adsorption ability of a native Jonesia quinghaiensis strain ZFSY-01, a microorganism isolated from uranium tailing wastewater, to U(VI) in wastewater under different conditions was studied in this work. The results showed that 391.5 mg U/g and 78.3% of adsorption capacity and efficiency were achieved under an optimum adsorption condition, respectively. Especially, the adsorption capacity of this strain reached the maximum (Q=788.9 mg U/g) under 100 mg/L of strain dosage. Simultaneously, the linear regression coefficients for the used isothermal sorption model indicate that the biosorption process is compatible with the Freundlich isotherm, the Temkin isotherm and the Halsey isotherm model. Based on the fitted kinetic parameters, the data from the experiments fit well with models of pseudo-second-order kinetics and intraparticle diffusion, suggesting that the strain ZFSY-01 immobilized U(VI) by physical and chemical adsorption. In addition, thermodynamic parameters demonstrated that the sequestration of U(VI) by the strain is spontaneous and endothermic. Based on the above analysis, strain ZFSY-01 can effectively remove U(VI) ions from high- or low-concentration uranium-containing wastewater and is expected to become a promising biological adsorbent. HIGHLIGHTS Specific microbes in special habitats have potential efficacy.; Adsorption capacity of strain ZFSY-01 reached 788.9 mg U/g under 100 mg/L of dosage.; Strain ZFSY-01 immobilized U(VI) by physical and chemical adsorption.; It is expected to be a green and efficient biosorbent material.;